163k views
5 votes
2m+7/4(3/4m-5/2)=3/32+1/3m

User Hareesh
by
5.0k points

2 Answers

1 vote

For this case we have the following equation:


2m + \frac {7} {4} (\frac {3} {4} m- \frac {5} {2}) = \frac {3} {32} + \frac {1} {3} m

We apply distributive property on the left side of the equation:


2m + \frac {21} {16} m- \frac {35} {8} = \frac {3} {32} + \frac {1} {3} m

We add similar terms from the left side:


\frac {53} {16} m- \frac {35} {8} = \frac {3} {32} + \frac {1} {3} m

Add
\frac {35} {8}to both sides:


\frac {53} {16} m = \frac {3} {32} + \frac {1} {3} m + \frac {35} {8}

We subtract
\frac {1} {3} m from both sides:


\frac {53} {16} m- \frac {1} {3} m = \frac {3} {32} + \frac {35} {8}\\\frac {143} {48} m = \frac {1144} {256}\\143m = \frac {1144 * 48} {256}

We simplify:


143m=(54912)/(256)\\143m=(13728)/(64)\\143m=(3432)/(16)\\143m=(858)/(4)\\143m=(429)/(2)

We divide between 143 on both sides:


m=(429)/(2*143)\\m=(429)/(286)\\m=(33)/(22)\\m=(3)/(2)

ANswer:


m=(3)/(2)

User KSev
by
4.5k points
2 votes

Answer:
m=(3)/(2)

Step-by-step explanation:

We have the following equation:


2m+(7)/(4)((3)/(4)m-(5)/(2))=(3)/(32)+(1)/(3)m

We need to isolate
m:


2m+(21)/(16)m-(35)/(8)=(3)/(32)+(1)/(3)m

Grouping similar terms:


2m+(21)/(16)m-(1)/(3)m=(3)/(32)+(35)/(8)


(143)/(48)m=(143)/(32)


m=(48)/(32)

Dividing the numerator and the denominator by 16:


m=(3)/(2)

User Timothy Nwanwene
by
4.9k points